Genome-Wide Single Nucleotide Polymorphism Analysis Elucidates the Evolution of Prunus takesimensis in Ulleung Island: The Genetic Consequences of Anagenetic Speciation - Cho, Myong-Suk; Takayama, Koji; Yang, JiYoung; Maki, Masayuki; Kim, Seung-Chul (Frontiers in Plant Science, 2021)
Of the two major speciation modes of endemic plants on oceanic islands, cladogenesis and anagenesis, the latter has been recently emphasized as an effective mechanism for increasing plant diversity in isolated, ecologically homogeneous insular settings. As the only flowering cherry occurring on Ulleung Island in the East Sea (concurrently known as Sea of Japan), Prunus takesimensis Nakai has been presumed to be derived through anagenetic speciation on the island. Based on morphological similarities, P. sargentii Rehder distributed in adjacent continental areas and islands has been suggested as a purported continental progenitor. However, the overall genetic complexity and resultant non-monophyly of closely related flowering cherries have hindered the determination of their phylogenetic relationships as well as the establishment of concrete continental progenitors and insular derivative relationships. Based on extensive sampling of wild flowering cherries, including P. takesimensis and P. sargentii from Ulleung Island and its adjacent areas, the current study revealed the origin and evolution of P. takesimensis using multiple molecular markers. The results of phylogenetic reconstruction and population genetic structure analyses based on single nucleotide polymorphisms detected by multiplexed inter-simple sequence repeat genotyping by sequencing (MIG-seq) and complementary cpDNA haplotypes provided evidence for (1) the monophyly of P. takesimensis; (2) clear genetic differentiation between P. takesimensis (insular derivative) and P. sargentii (continental progenitor); (3) geographic origin of P. takesimensis via single colonization from the source population of P. sargentii in the Korean Peninsula; (4) no significant reduction in genetic diversity in anagenetically derived insular species, i.e., P. takesimsnsis, compared to its continental progenitor P. sargentii; (5) no strong population genetic structuring or geographical patterns in the insular derivative species; and (6) MIG-seq method as an effective tool to elucidate the complex evolutionary history of plant groups.